Causal association between inflammatory bowel disease and herpes virus infections: a two-sample bidirectional Mendelian randomization study - Zou, Menglong; Zhang, Wei; Shen, Lele; Xu, Yin; Zhu, Ying (Frontiers in Immunology, 2023)
Background: Previous observational or retrospective studies have suggested an association between inflammatory bowel disease (IBD) and herpes virus infections. Using Mendelian randomization (MR) approach, our objective was to determine whether there was a causal association between IBD and herpes virus infections. Methods: In genome-wide association study (GWAS) datasets of the International Inflammatory Bowel Disease Genetics Consortium, we obtained genetic instrumental variables for three phenotypes from 34,652 participants (12,882 IBD cases and 21,770 controls), 27,432 participants [6,968 ulcerative colitis (UC) cases and 20,464 controls], and 20,883 participants [5,956 Crohn's disease (CD) cases and 14,927 controls], respectively. Summary statistics for herpes virus infections (chickenpox, herpes zoster, and mononucleosis) were obtained from the FinnGen database. MR results were expressed as odds ratio (OR) with 95% confidence interval (CI). Results: Our study found no evidence of a causal effect of genetically predicted IBD on herpes virus infections [P value for inverse variance weighting (IVW): 0.063 to 0.652]. For the subtypes of IBD, UC had a suggestive association with mononucleosis (P value for IVW: 0.023). It appeared that CD was also weakly associated with mononucleosis (P value for IVW: 0.058; P value for Weighted median: 0.036). In addition, we found a suggestive causality for CD on chickenpox (P value for IVW: 0.038). Neither UC (P value for IVW: 0.574) nor CD (P value for IVW: 0.168) has a causal effect on herpes zoster. The results of the bidirectional MR analysis did not indicate that herpes virus infections were associated with IBD, UC or CD (P value for IVW: 0.239 to 0.888). Conclusion: This study showed a suggestive causality for both CD-chickenpox and UC-mononucleosis, despite no associations reaching a statistical significance value after corrections for multiple testing. There was no evidence of a causal association between IBD and its two subtypes on herpes zoster.